Improving Students Reading Comprehension Through Intensive Reading for College Students - Dadan Hidayat (Politeknik Negeri Bengkalis, 2023)
This study aims to see the improving students' reading comprehension through intensive reading for college students. The quantitative method was applied by the writer for this research since the writer required the data to be examined using a statistically oriented method, specifically statistics. The writer then used the quantitative research method to administer the test for this study, and the data was evaluated by assessing the relationship between variables For experimental research, the writer used the quasi-experiment because quasi suited to look at the effect of an educational intervention, such as a school improvement program, a project to improve a specific element (such as an anti-bullying program), or a professional development programed. intensive reading improves students' reading comprehension. It was demonstrated by the student's grade. The mean post-test pre-test score, in addition to the student's enthusiasm during the observation of the reading process, when intense reading is implied in the class, indicates that intensive reading will assist the teacher in increasing students' reading comprehension